A Cross-Sectional Study on Potential Ovarian Volume and Related Factors in Women with Polycystic Ovary Syndrome from Infertile Couples - Le NSV; Le MT; Nguyen ND; Tran NQT; Nguyen QHV; Cao TN (Dove Medical Press, 2021)
Nguyen Sa Viet Le,1,2 Minh Tam Le,2,3 Nguyen Dac Nguyen,2,3 Nhu Quynh Thi Tran,3 Quoc Huy Vu Nguyen,2 Thanh Ngoc Cao2,3 1Department of Assisted Reproduction, Hue Central Hospital, Hue, Vietnam; 2Department of Obstetrics and Gynecology, Hue University of Medicine and Pharmacy, Hue University, Hue, Vietnam; 3Center for Reproductive Endocrinology and Infertility, Hue University of Medicine and Pharmacy, Hue University, Hue, VietnamCorrespondence: Minh Tam Le Email leminhtam@huemed-univ.edu.vnPurpose: This study was designed to explore the value of ovarian volume (OV) measured by transvaginal ultrasound and its relationship with anthropometry and serum hormonal levels in a polycystic ovary syndrome (PCOS) population.Patients and Methods: A total of 119 women with PCOS from infertile couples were recruited in this cross-sectional study. On days 2- 4 of the menstrual cycle, transvaginal ultrasound examinations were performed, and hormonal profiles were measured. PCOS diagnosis was based on the Rotterdam 2003 criteria and classified into four phenotype groups. The PCOS group (study group) and the non-PCOS group (control group) were compared.Results: The mean age of the participants was 32.66± 4.10 years compared to 33.99± 4.78 years in 273 cases (69.6%) without PCOS. The mean OV was statistically larger in the PCOS group than in the non-PCOS group (7.65± 3.23 mL vs 6.08± 3.67 mL, p < 0.001) and positively correlated with serum anti-Mullerian (AMH) and luteinizing hormone (LH) levels (r=0.30; p < 0.001 and r=0.23; p < 0.001, respectively), and weakly and inversely correlated with age (− 0.182, p < 0.001). The area under the receiver operating characteristic (ROC) curve of OV in the diagnosis of PCOS was 0.613 (0.557- 0.670, 95% CI).Conclusion: The enlarged OV is remarkable in women with PCOS and is related to AMH and LH concentrations. Although the diagnostic potential of PCOS is substantially low, OV alone may contribute to predicting the severity of PCOS and better performance for the diagnosis of PCOS phenotypes.Keywords: ovarian volume, anti-Mullerian hormone, PCOS phenotypes, diagnose, infertility